تدويل الدساتير وأثره على سيادة الدولة - بن صديق, فتيحة; هاملي, محمد (جامعة الوادي.University eloued, 2021)
لقد نتج عن تصاعد تطور القانون الدولي بروز نظام عالمي يحمل قيما جديدة كالديمقراطية وحقوق الانسان، تبنتها جل الدول بتضمينها في دساتيرها. والتزايد في وتيرة تسلل القانون الدولي إلى قواعد الدستور، هو نتاج لظاهرة تدويل الدساتير الّتي تؤدي إلى تغيير تنظيم السلطات العامة في الدولة وعلاقاتها ببعضها البعض، وعلاقة كل منها بالأفراد، وتقوية المركز القانوني لهؤلاء داخل الدولة، كما تساهم في امتداد القانون الدولي إلى مجالات تعتبر من الاختصاصات الداخلية للدولة، بما ينعكس على مبدأ سمو الدستور. وبهذا فإنّ مفهوم السّيادة المرتبط بهذا السمو قد تأثر إلى حد كبير بهذه التغييرات، وأصبح يتحدد نطاق السيادة بالتزام الدولة بأحكام المجتمع الدولي. The rise in the development of international law has resulted in the emergence of a world order that holds new values such as democracy and human rights, which most States have embraced by incorporating them into their constitutions. The increasing rate of infiltration of international law into the rules of the Constitution is the result of the phenomenon of the internationalization of constitutions, which changes the organization of the State's public authorities, their relations with each other, their relationship with individuals, and the strengthening of their legal status within the State. It also contributes to the extension of international law into areas considered the internal competence of the State, which affects the principle of the primacy of the Constitution. The concept of sovereignty associated with this transcendence had thus been greatly influenced by these changes, and the scope of sovereignty is now determined by the commitment of the State to the provisions of the international community.
المجلد 12 والعدد 02
Keywords: القانون الدولي ; القانون الداخلي ; تدويل الدساتير ; الاختصاصات الداخلية ; سيادة الدولة; the international law ; internal law ; the internationalization of constitutions ; domestic competence ; the state sovereignt